2020
DOI: 10.1186/s12885-020-07607-5
|View full text |Cite|
|
Sign up to set email alerts
|

A Bibliometric analysis of folate receptor research

Abstract: Background The objective of this study was to conduct a bibliometric analysis of the entire field of folate receptor research. Folate receptor is expressed on a wide variety of cancers and certain immune cells. Methods A Web of Science search was performed on folate receptor or folate binding protein (1969-to June 28, 2019). The following information was examined: publications per year, overall citations, top 10 authors, top 10 institutions, top 10 cited articles, top 10 countries, co-author collaborations an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…They have also shown that GNVs can carry specific therapeutic agents, such as DNA, proteins, and short interfering RNAs (siRNAs), and can be modified to specifically target tumor tissues. As a proof of concept, they demonstrated that GNVs carrying Pentoxifylline (PTX), an anti-cancer drug [64], and binding folic acid (FA), which was chosen because many tumors have a high expression of folate receptors [65], were able to target and decrease tumor growth in in vivo model [63].…”
Section: Pdevs As Drug Delivery Vehiclesmentioning
confidence: 99%
“…They have also shown that GNVs can carry specific therapeutic agents, such as DNA, proteins, and short interfering RNAs (siRNAs), and can be modified to specifically target tumor tissues. As a proof of concept, they demonstrated that GNVs carrying Pentoxifylline (PTX), an anti-cancer drug [64], and binding folic acid (FA), which was chosen because many tumors have a high expression of folate receptors [65], were able to target and decrease tumor growth in in vivo model [63].…”
Section: Pdevs As Drug Delivery Vehiclesmentioning
confidence: 99%
“…Although the research on PCOS has been deepening in recent years, the number of research articles is insufficient to cover PCOS, which has such a high incidence. The average number of cited articles in PCOS was only 4–5 per year, which still represents a large gap compared with other studies [ 24 , 25 ]. This number of articles shows that the influence of PCOS is insufficient at present.…”
Section: Discussionmentioning
confidence: 71%
“…More than 467 articles were searched from Web of Science (WoS) with the keywords of [top-cited or (top and cited)] in the title. Coword analysis [26][27][28] and author collaborations [29][30][31] were applied in most articles separately in bibliometrics. Few studies combined the 2 analyses (e.g., assigning themes to author clusters) in their studies.…”
Section: Classifications Of Scs Are Required In 100 Top-cited Articlesmentioning
confidence: 99%